O significado do curso do Pronatec e a inserção no mercado de trabalho do jovem egresso do programa - Ananias, Lucas Andrade (2015)
This work is located in the Research Line "School Practice and Public Policy" of the Education Post Graduation Program of the Federal University of Santa Maria. By focusing on the National Program for Access to Technical Education and Employment (PRONATEC), it reflects the problem: Which are the impacts of PRONATEC in life and integration of young people into the labor market? . This scientific investigation had as general objective analyze the impacts of PRONATEC in life and integration of young people into the labor market. Specific objectives: To identify the profile of young people graduates of PRONATEC courses; To check the evaluation of young people in relation to courses offered by PRONATEC; To search the impact of PRONATEC in the lives of young people graduates of the program. The phenomenon was analyzed quantitative/qualitative by the analyze of 415 registration files of young people graduates of five Continuing Initial Training courses of PRONATEC in a System S institution of the city of Santa Maria RS. The registration files submitted information such as gender, marital status, ethnicity, educational level and occupational status of young people. Also an interview with 8 young people in which they discussed issues such as youth, education, labor, the strengths and weaknesses of the course and the PRONATEC contribution in the professional qualification. The theoretical analysis and data analysis were based on studies of authors such as Abramo (1997, 2005), Carrano (2010), Cassiolato and Garcia (2014), Corrochano (2008, 2013, 2014), Faleiros (2006), Gonzalez (2009), Leite (2003), Melucci (1997), Sposito and Carrano (2003), among others. Some findings: it was found that young people seek in the course of PRONATEC a possibility of rapid integration in the labor market; the importance of the certification, although this is not a guarantee of employment; the fact that training in these courses are still focused on the development of specific activities without developing in the young people the construction of critical thinking; and the necessity to offer courses that consider the needs of young people and the local economy.